Tag questions in fluent aphasia. An approximation from clinical sociolinguistics - Guillén Escamilla, Josaphat Enrique (Revista de Investigación en Logopedia, 2023)
This paper has two main aims, (i) to characterize the functions of tag questions in two speakers with fluent aphasia, and (ii) to contrast these results with a sample of two speakers without aphasia with similar social features. Our interest is, on the one hand, determine if individuals with aphasia use these elements to a greater, equal, or lesser extent, and, on the other hand, describe if there are similarities in the functions and in the kind of tag questions that are used in both samples. Thus, two samples were built, first one included two speakers diagnosed with fluent aphasia, and the second one was picked up from volume 3 of Corpus Sociolingüístico de la Ciudad de México (Martín Butragueño y Lastra, 2015), having as parameter the social features of the speakers with aphasia. The results indicate that: (i) tag questions are preserved despite of aphasia, (ii) the speakers with aphasia use them more frequently to carry out functions of: continuative, gestion of phatic interaction, focalizer, intensifier, and element of positive courtesy, and (iii) the question tags more usual in the variant of Mexico City’s Spanish –¿no?, ¿verdad?, and ¿eh?– are used by both groups. Finally, it is highlighting importance of include in clinical linguistics research a group of control with similar social features to group with aphasia to compare the real uses of communicative competence of these patients.